Developing a rehabilitation programme for male urinary incontinence: detailed schemes and results on 122 patients. Issue 3 (17th February 2015) - Terzoni, Stefano; Montanari, Emanuele; Mora, Cristina; Ricci, Cristian; Destrebecq, Anne
ABSTRACT Urinary incontinence (UI) is a common complication of prostatectomy. International guidelines suggest using pelvic floor muscle training (PFMT) as a first‐line intervention (grade A) to help patients reduce the involuntary urine leakages. In the literature it is hard to find a complete exercise scheme, with full details (e.g. body position during PFMT, how to avoid antagonist synergies), information on how to make exercises progressively more difficult, and data showing the efficacy of the whole programme. This study presents a complete PFMT programme, with full details and outcomes. A scheme of five progressive exercises was built, each with precise characteristics and times. Totally 131 patients with stress UI after radical retropubic prostatectomy were enrolled and followed a written scheme of PFMT with the five exercises. Leakages were quantified using the 24‐h pad test. Rehabilitation ended when patients had leakages less than 10 g/d. Nine patients could not achieve results and decided to exit the programme after a median of five sessions (InterQuartile Range, IQR = [4;7]). Out of the 122 patients, 90 patients who followed the full programme achieved the rehabilitation (70.3%); they had median leakages of 150 g, IQR = [90;300]. Those who did not reach the result had higher leakages [540 g/d, IQR = (300;840)] but obtained clinically significant reduction and reached a median of 90 g/d, IQR = [90;157] after comparable rehabilitation times (median of 6 or 7 sessions, corresponding to 8 or 10 weeks, for rehabilitated and non‐rehabilitated patients, respectively). Future studies will investigate the long‐term results of this programme.